Innovative spectroscopic and chromatographic techniques for the analysis of complex polyolefins prepared by metallocene catalysis - Graef, Sven Markus (Stellenbosch : Stellenbosch University, 2012)
Thesis (PhD)--Stellenbosch University, 2002.